Максимізація чистого прибутку - джерело зростання економічного потенціалу молокопереробних підприємств - Гнатенко, Є.П. (Культура народов Причерноморья, 2013)
У статті здійснено дослідження формування чистого прибутку на п’яти найбільших
молокопереробних підприємствах Миколаївської області. Позначені причини отримання деякими
підприємствами чистого збитку. Для максимізації чистого прибутку розроблена економіко-
математична модель. На основі оптимального обсягу і структури виробництва і реалізації продукції
визначена максимальна сума чистого прибутку, зростання економічного потенціалу молокопереробного
підприємства, а також необхідний обсяг закупівлі молокосировини. В статье проведено исследование формирования чистой прибыли на пяти крупных
молокоперерабатывающих предприятиях Николаевской области. Обозначены причины получения
некоторыми предприятиями чистого убытка. Для максимизации чистой прибыли разработана
экономико-математическая модель. На основе оптимального объема и структуры производства и
реализации продукции определена максимальная сумма чистой прибыли, рост экономического
потенциала молокоперерабатывающего предприятия, а также необходимый объем закупки
молокосырья. Activities can not be effective if the company receives damages. An important indicator for
determining the efficiency of dairy companies is the absolute amount of profit including earnings from
operations. In addition, the development of enterprises provided a net profit.In the article the study of the
formation of the net profit for the five major dairy establishments Mykolaiv region. Identified the reasons for
getting a net loss of some enterprises. In order to maximize profits dairy company proposed to increase the
volume of production and sales of products and review product strategy. Using economic - mathematical model
based on indicators: production volume by product, the cost and the price of 1 ton of each product, the net profit
of each type of commodity products, the forecast of production and sales by product for the enterprise. In this
regard, net profit growth of over 70%, which contributes to the growth of the economic potential of the
enterprise. Furthermore, based on the data model defines the required purchase amount of milk. Implemented a
general forecast consumption of milk on the production of specific types of products. The total amount of net
profit may be directed to the development of the resource base.